Landmarks of Identity: Bronze Age Towers of the Oman Peninsula - Döpper, Stephanie (Archaeopress, 2024)
Five thousand years ago, in the Early Bronze Age, monumental stone and mud-brick structures known as towers appeared on the landscape of the Oman Peninsula. Since then, they have served as distinctive landmarks of identity for the people of the region. Despite many years of archaeological research and intensive excavations of some of them, much remains unknown about these impressive structures. This book aims to update the long-standing discussions on these towers and to assess their chronological depth of more than a millennium, with the first of them constructed as early as the end of the 4th millennium BCE and the last substantial building activities at the beginning of the 2nd millennium BCE. The book also reassesses their possible functions, such as defence, refuge, demarcation of property, residence of elites, involvement in complex irrigation systems, arenas for cultic practices, in the light of recent archaeological research. The book will also provide a richly illustrated catalogue with extensive bibliography, research history and coordinates of all the nearly hundred towers known to date in the Sultanate of Oman and the United Arab Emirates, creating a record for researchers and visitors alike.
Keywords: Archéologie – Oman

Landmarks of Identity: Bronze Age Towers of the Oman Peninsula - Döpper, Stephanie (Archaeopress, 2024)
Five thousand years ago, in the Early Bronze Age, monumental stone and mud-brick structures known as towers appeared on the landscape of the Oman Peninsula. Since then, they have served as distinctive landmarks of identity for the people of the region. Despite many years of archaeological research and intensive excavations of some of them, much remains unknown about these impressive structures. This book aims to update the long-standing discussions on these towers and to assess their chronological depth of more than a millennium, with the first of them constructed as early as the end of the 4th millennium BCE and the last substantial building activities at the beginning of the 2nd millennium BCE. The book also reassesses their possible functions, such as defence, refuge, demarcation of property, residence of elites, involvement in complex irrigation systems, arenas for cultic practices, in the light of recent archaeological research. The book will also provide a richly illustrated catalogue with extensive bibliography, research history and coordinates of all the nearly hundred towers known to date in the Sultanate of Oman and the United Arab Emirates, creating a record for researchers and visitors alike.
Keywords: Archéologie – Oman

Hafit period fuelwood preferences associated with early copper production at Building V, al-Khashbah, Oman - Proctor, Lucas; Döpper, Stephanie; Schmidt, Conrad (Proceedings of the Seminar for Arabian Studies, 2024)
Analyses of archaeological fuel remains can provide insight into pyrotechnologies, resource management, and the local environment. In this paper, we examine archaeological charcoals from Hafit period (3300–2700 BC) levels in Building V at al‑Khashbah (al-Khashaba), Oman, to understand fuel harvesting and burning preferences associated with early copper production. Building V is currently thought to be the earliest identified copper-production site in Oman based on the presence of abundant pyrotechnological remains, copper slag, and stratified radiocarbon results. Here, we build on previous anthracological work reconstructing woodland composition from the site. Anthracologists are increasingly recognising that fuelwood collection is often based on social or functional grounds rather than species availability. To that end, we have combined traditional taxonomic analysis with the application of dendro-anthracological methods to examine how intensive wood harvesting was for copper production and whether it had effects on the local vegetation. Dendrological reconstruction of wood calibre and condition at burning combined with spatial patterning of remains provides a more nuanced view of these preferences than can be achieved through taxonomic analysis alone.
Keywords: Archéologie – Oman